Measurement of Economic Development and Interdependence of Countries - Korganashvili, Larisa (European Journal of Multidisciplinary Studies, 2016)
At the present time to assess countries economic development, mostly used indicators are per capita GDP and GDP. However, these indicators do not sufficiently reflect the level of economic development of countries. In this regard, for clarification of GDP a correction factor and to determine the interdependence of countries - the interdependence factors are proposed.